2022
DOI: 10.1111/1346-8138.16533
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil‐to‐lymphocyte ratio is a potential prognostic biomarker for extramammary Paget disease: A retrospective study

Abstract: Extramammary Paget disease (EMPD) is a rare, cutaneous malignancy that may occur in the genital and perianal regions in persons aged >60 years. 1 The incidence rate of EMPD in the United States has increased from approximately 0.3 per 10 million population in 1973 to more than 10 times that rate in 2013. 2 Prognosis of EMPD without distant metastasis is favorable, with a 5-year survival rate of 84%. However, once distant metastases occur, this rate falls to 7%. 3 Several studies have shown that cytotoxic antic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Significantly higher NLR values were found in patients with metastatic compared to non-metastatic EMPD at the time of evaluation (mean: 3.39 vs. 2.53; p < 0.005). Moreover, the NLR was an independent prognostic factor for overall survival ( p = 0.019) as well as an independent predictor of survival among EMPD patients with metastatic disease ( p = 0.036) [ 46 ]. In a follow-up multivariate analysis that included 85 patients with EMPD, the same authors found that NLR and a higher invasion level were the two independent predictive factors for SLN biopsy positivity [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Significantly higher NLR values were found in patients with metastatic compared to non-metastatic EMPD at the time of evaluation (mean: 3.39 vs. 2.53; p < 0.005). Moreover, the NLR was an independent prognostic factor for overall survival ( p = 0.019) as well as an independent predictor of survival among EMPD patients with metastatic disease ( p = 0.036) [ 46 ]. In a follow-up multivariate analysis that included 85 patients with EMPD, the same authors found that NLR and a higher invasion level were the two independent predictive factors for SLN biopsy positivity [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…The diagnosis of EMPD is frequently delayed, causing older age of patients at diagnosis, which results in decreased survival ( 5 ). Thus, a series of studies focused on the dissection of EMPD pathogenesis of EMPD and biomarkers identification such as neutrophil-to-lymphocyte ratio ( 21 ). Metabolomics is becoming a powerful omics tool, which has been successfully applied to various cutaneous carcinoma including melanoma ( 22 ), cutaneous squamous cell carcinoma ( 23 ), and basal cell carcinoma ( 24 ).…”
Section: Discussionmentioning
confidence: 99%